The Other Side of Gravity and Geometry: Antigravity and Anticurvature - M. I. Wanas (Advances in High Energy Physics)
Gravity is one of the four known fundamental interactions used to study and interpret physical phenomenae. It governs diverse phenomenae, especially those connected with large-scale structures. From more than one decade, existing gravity theories have suffered from some problems, when confronting their predictions with the results of some experiments and observations. This situation has led to many suggestions, none of which is final, so far. Here, we show that the assumption of existence of another side of gravity, a repulsive gravity or antigravity, together with its attractive side, may give a satisfactory solution to gravity problems. We caught here two pieces of evidence for the existence of antigravity in nature. The first is on the laboratory scale, the COW experiment, and the second is on the cosmic scale, SN type Ia observation. On the other hand, we show how gravity theories can predict antigravity, using a new defined geometric object called Parameterized anticurvature. This shows clearly how Einstein's geometrization philosophy can solve recent gravity problems in a satisfactory and easy way. Also, it may throw some light on the mystery of physical nature of “Dark Energy.”